2021
DOI: 10.1021/acs.inorgchem.1c02339
|View full text |Cite
|
Sign up to set email alerts
|

Group IV Transition Metal (M = Zr, Hf) Precursors for High-κ Metal Oxide Thin Films

Abstract: This paper describes the synthesis of eight novel zirconium and hafnium complexes containing N-alkoxy carboxamidate-type ligands, as potential precursors for metal oxides and atomic layer deposition (ALD) for HfO 2 . A series of ligands, viz., Nethoxy-2,2-dimethylpropanamide (edpaH), N-ethoxy-2-methylpropanamide (empaH), and N-methoxy-2,2-dimethylpropanamide (mdpaH), were used to afford complexes Zr(edpa) 4 (1), Hf(edpa) 4 (2), Zr(empa) 4 (3), Hf(empa) 4 (4), Zr(mdpa) 4 (5), Hf(mdpa) 4 (6), ZrCp(edpa) 3 ( 7), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The OC H 2 CH 3 of the ethoxy group in 4 – 6 shifted downfield relative to those of the relevant starting materials L 4 – L 6 (from 3.93 to 4.08 ppm for 4 , from 3.86 to 4.06 ppm for 5 , and from 3.86 to 4.06 ppm for 6 ), thereby indicating that the oxygen in the electron donor was coordinated to the antimony atom. The imine peak of all complexes in the 13 C NMR spectrum showed peaks in the range of 163.66–168.38; this range is similar to that observed for previously reported homoleptic metal monomer complexes using these types of ligands. , These observations confirmed that the ligand was attached via a desalted oxygen atom to the antimony metal center.…”
Section: Resultssupporting
confidence: 87%
“…The OC H 2 CH 3 of the ethoxy group in 4 – 6 shifted downfield relative to those of the relevant starting materials L 4 – L 6 (from 3.93 to 4.08 ppm for 4 , from 3.86 to 4.06 ppm for 5 , and from 3.86 to 4.06 ppm for 6 ), thereby indicating that the oxygen in the electron donor was coordinated to the antimony atom. The imine peak of all complexes in the 13 C NMR spectrum showed peaks in the range of 163.66–168.38; this range is similar to that observed for previously reported homoleptic metal monomer complexes using these types of ligands. , These observations confirmed that the ligand was attached via a desalted oxygen atom to the antimony metal center.…”
Section: Resultssupporting
confidence: 87%
“…Recently, to overcome this, alkoxide ligands with additional functionalized donors have been used as bidentate ligands in ALD processes for metal oxide thin films. The bidentate ligands that have been widely studied for ALD thin films of ZrO 2 and HfO 2 are alkoxyalkoxides, such as 1-methoxy-2-methyl-2-propanolate (mmp), , as well as aminoalkoxides, such as dimethylaminoethoxide (dmae) and 1-dimethylamino-2-methyl-2-propoxide (dmamp). In the previous study, we discussed new high-κ metal precursors for Zr and Hf oxide containing N -alkoxy carboxamides as bidentate ligands and ALD applications using a novel hafnium precursor …”
Section: Introductionmentioning
confidence: 99%
“…21−23 In the previous study, we discussed new high-κ metal precursors for Zr and Hf oxide containing Nalkoxy carboxamides as bidentate ligands and ALD applications using a novel hafnium precursor. 24 With this knowledge, we have focused on the synthesis of new zirconium and hafnium precursors containing modified bidentate donor�functionalized alkoxide ligands to coordinatively saturate the metal center and hence improve the volatility and thermal stability of the metal precursor. While searching for new bidentate ligands for zirconium and hafnium oxide precursors, we decided to introduce amidoxime ligands, which are analogues of an oxime with one of the substituents being an amino group, expecting that these ligands would improve the new zirconium and hafnium complexes' thermal stability and volatility.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations